Teach yourself visually Office 2010 - Shoup, Kate, 1972- (Indianapolis, Ind. : Wiley Pub., Inc., 2010)
"Are you a visual learner? Do you prefer instructions that show you how to do something--and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 220 Office 2010 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Office 2010 in no time"--Cover, p. 4.
Ch. 1 Office basics -- Ch. 2 Working with files -- Ch. 3 Office graphics tools -- Ch. 4 Working with office files online -- Ch. 5 Adding text -- Ch. 6 Formatting text -- Ch. 7 Adding extra touches -- Ch. 8 Reviewing documents -- Ch. 9 Building spreadsheets -- Ch. 10 Worksheet basics -- Ch. 11 Working with formulas and functions -- Ch. 12 Working with charts -- Ch. 13 Creating a presentation -- Ch. 14 Populating presentation slides -- Ch. 15 Assembling and presenting a slide show -- Ch 16. Database basics -- Ch. 17 Adding, finding and querying data -- Ch. 18 Organizing with Outlook -- Ch. 19 E-mailing with Outlook -- Ch. 20 Publisher basics -- Ch. 21 Fine-tuning a publication -- Ch. 22Taking notes with OneNote -- Ch. 23 Organizing and sharing notes.
Includes index.
Keywords: Microsoft Office; Business -- Computer programs